Two types of nitrito support for μ4-oxido-bridged [Cu4] complexes: synthesis, crystal structures, magnetic properties and DFT analysis1. Issue 13 (7th April 2015) - Pait, Moumita; Shatruk, Michael; Lengyel, Jeff; Gómez-Coca, Silvia; Bauzá, Antonio; Frontera, Antonio; Bertolasi, Valerio; Ray, Debashis
<x xml:space="preserve">Abstract</x> In situ generated NO2− and externally added NO2− and AcO− ions have been utilized for the isolation of μ4-oxido-bridged Cu4 aggregates showing magnetic coupling which can be rationalized by DFT calculations.